2018
DOI: 10.2147/cmar.s187061
|View full text |Cite
|
Sign up to set email alerts
|

Liver surgery prolongs the survival of patients with gastrointestinal stromal tumor liver metastasis: a retrospective study from a single center

Abstract: ObjectivesGastrointestinal stromal tumor (GIST) liver metastasis (GLM) is a special subset of advanced GIST, because its lesions are easier to define and assess. We aim to determine the role of liver metastasectomy for patients with GLM in the era of tyrosine kinase inhibitor (TKI) therapy.MethodsWe reviewed patients with metastatic GIST who received surgery or other treatments in Sun Yat-sen University Cancer Center between January 1991 and December 2017. Patients with metastases confined to the liver and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…In the propensity model, addition of surgery was still associated with better PFS and OS in both univariate and multivariate analyses. Previous studies reported a 3y PFS of 25.6%-77.5% for patients receiving surgery for liver metastases from GIST, which is inferior to our result (17,19,22,25,26). The difference in survival is probably attributed to the inclusion of patients with more advanced disease such as extrahepatic metastases and imatinib resistance in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the propensity model, addition of surgery was still associated with better PFS and OS in both univariate and multivariate analyses. Previous studies reported a 3y PFS of 25.6%-77.5% for patients receiving surgery for liver metastases from GIST, which is inferior to our result (17,19,22,25,26). The difference in survival is probably attributed to the inclusion of patients with more advanced disease such as extrahepatic metastases and imatinib resistance in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…A Japanese prospective, multicenter trial was once conducted to clarify the efficacy and safety of surgery for liver oligometastasis but was prematurely terminated due to the amendment of the guideline and poor accrual (18). Several retrospective studies conducted in the last decade have indicated survival benefit from adding hepatectomy in the treatment of metastatic GIST, but were limited statistically by small sample size as well as their heterogeneity (19)(20)(21)(22)(23)(24)(25)(26). To better demonstrate the clinical benefit of hepatectomy, we adopted strict inclusion criteria and collected a relatively homogenous cohort of patients with liver metastases from GIST.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 studies [25][26][27][28][29][30][31][32][33][34] including 1119 patients (361 patients in the surgery group and 758 patients in the no surgery group) met the eligibility criteria and were included in the nal analysis (Figure 1). Manual searches of the references lists of the included studies did not yield any further studies.…”
Section: Study Selection and Qualitymentioning
confidence: 99%
“…Studies that contain patients with PD were excluded. A total of 7 studies 25,[28][29][30][31][32]34 including 863 patients (240 patients in the surgery group and 621 patients in the no surgery group) were included in the subgroup analyses. Subgroup analysis results were consistent with the overall results (OS: HR, 0.67; 95% CI, 0.55 to 0.81; P < 0.0001; Figure 3A; PFS: HR, 0.62; 95% CI, 0.46 to 0.82; P = 0.009; Figure 3B).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation